More valuable dead than deterred? Crop‐raiding bears in Lao PDR. (20th August 2014) - Scotson, Lorraine; Vannachomchan, Kongseng; Sharp, Thomas
ABSTRACT Human–bear conflicts may contribute to population declines of Asiatic black bears (Ursus thibetanus) and sun bears (Helarctos malayanus) in Southeast Asia. We investigated crop‐raiding behaviors by bears and responses from affected farmers in and around a protected area in northern Lao PDR during August–October 2011. We interviewed farmers and made visual inspections of raided fields in 6 villages. Villagers reported that more crops were lost to bears than to all other wildlife species combined. Commercial and local sweet corn fields were the most commonly damaged. Perceived crop damage by bears varied widely among villages (11‐39% of total area) and individual farmers (1–90%). Farmers' estimates of the extent of bear crop damage were higher than our estimates of the same fields. Although farmers reported Asiatic black bears as more common crop‐raiders than sun bears, this assessment is suspect, because bears were reported to raid fields exclusively at night. Locals used a wide range of mainly ineffective methods to deter bears from crops. Clearing paths around crop fields was most common (approx. 90% of farmers). Few farmers admitted using snares to remove offending bears, because this is illegal. However, the collective evidence indicates that snaring does occur, and farmers would gain more by killing and selling bears for their parts than by protecting their fields from bear damage. This may explain the unexpected finding that most farmers (approx. 90%) said they liked bears in the area, and did not report damage to authorities. Consequently, they may not be motivated to try or maintain new deterrent techniques. © 2014 The Wildlife Society.